Do firms with works councils prefer agreeable job applicants? A discrete choice experiment - Harald Pfeifer; Caroline Wehner; Andries de Grip; Julia M. Kensbock (Industrial Relations: A Journal of Economy and Society, 2024)
Works councils in many countries are involved in dismissal procedures and may therefore invoke high hold-up costs for firms laying off workers. To avoid these conflicts, firms with a works council may have a stronger preference for more agreeable job applicants who have a low risk of dismissal. We conduct a discrete choice experiment among recruiters to assess their preferences regarding job applicants' personality traits and competence. In line with our expectations, we find that recruiters from works-council firms more strongly prefer agreeable job applicants. We also find that more agreeable recruiters choose more agreeable employees, indicating a similarity-attraction effect.
Keywords: 330